Calidad del servicio financiero y su relación con la inclusión financiera en clientes del Banco de la Nación año 2024 - Ahuanari Saavedra, Amanda Victoria (2025)
In Peru, dissatisfaction with banking services and low financial inclusion are interrelated problems that affect a large part of the population and the consequences are profound and multifaceted, negatively impacting both individuals and the economy in general. Therefore, the present research aims to identify how the quality of financial service and financial inclusion are related in clients of the Banco de la Nación in 2024, from a quantitative approach of a descriptive observational type and a non-experimental correlational design, with a population made up of 120 users of the Banco de la Nación, the results revealed a positive and significant relationship, with a Spearman coefficient of 0.689 (p = 0.000), indicating a moderately strong relationship. This implies that improvements in the quality of service are associated with an increase in financial inclusion, a key factor in expanding opportunities for access to financial products that promote the economic stability of users. It was observed that 62% of customers perceive a high level of quality, highlighting aspects such as speed and efficiency in service (53%), cleanliness and comfort of facilities (55%) and accuracy in transactions (42%). Regarding financial inclusion, 71% positively valued this dimension, highlighting the ease of opening bank accounts (58%), clarity in credit terms (52%) and the use of digital tools such as mobile applications (55%).